Les risques du journalisme dans les conflits armés - Aimé-Jules Bizimana (Communication)
The resurgence of attacks on the security of journalists during the recent conflict in Iraq opened a debate on the conditions under which the profession can be exercised in situations of armed conflict. Journalists, editors-in-chief, and professional associations have been called on to examine the necessity of journalistic presence in conflicts, the level of danger implied by this presence, and the appropriate ways of diminishing it. This article examines the question of the risks of journalism in times of conflict by resituating it in the general framework of risk society as described by sociologists Ulrich Beck and Anthony Giddens.